MANAJEMEN KURIKULUM PENDIDIKAN ISLAM DAN PESANTREN - Sudarsono Sudarsono (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2020)
For educational institutions that hone the social and mental attitudes ofstudents with a unique, character-driven model of coaching, with itssimplicity, pesantren has been able to produce graduates who are ready totake part and withstand the challenges and temptations that hinder theirstruggles. uphold scientific and religious values. Management of organizingand implementing the curriculum with regard to all actions related to thedetailing and distribution of all possible tasks to be carried out. In curriculumimplementation management aims to ensure that the curriculum can beimplemented properly. In this case, the management is tasked with providingmaterial, personal facilities and conditions so that the curriculum can beimplemented.